2018
DOI: 10.1074/jbc.ra117.000795
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine increases HIV infectivity in neural progenitor cells

Abstract: HIV-1 infection and methamphetamine (METH) abuse frequently occur simultaneously and may have synergistic pathological effects. Although HIV-positive/active METH users have been shown to have higher HIV viral loads and experience more severe neurological complications than non-users, the direct impact of METH on HIV infection and its link to the development of neurocognitive alternations are still poorly understood. In the present study, we hypothesized that METH impacts HIV infection of neural progenitor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 73 publications
3
35
0
Order By: Relevance
“…In our experiments, exposure to HIV-ECVs increased NeuN positive cell number. These results are in line with the literature reports demonstrating that NPCs could be infected with HIV (73)(74)(75) and HIV affected their proliferation and survival in vitro and in vivo (73,76).…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments, exposure to HIV-ECVs increased NeuN positive cell number. These results are in line with the literature reports demonstrating that NPCs could be infected with HIV (73)(74)(75) and HIV affected their proliferation and survival in vitro and in vivo (73,76).…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments, exposure to HIV-ECVs increased NeuN positive cell number. These results are in line with the literature reports demonstrating that NPCs could be infected with HIV [73][74][75] and HIV affected their proliferation and survival in vitro and in vivo [73,76]. Moreover, the number of hippocampal NPCs in postmortem brains in HIV patients with dementia was lower when compared to patients without dementia [26].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in in vitro models have demonstrated that Meth enhances HIV-1 replication in T-cells, DCs, macrophages and neural progenitor cells 1114 . The significance of these results is supported by an epidemiological study, which demonstrated increased viral loads in Meth using HIV-1 infected individuals compared with non-users who were infected 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Further, Meth has been shown to enhance HIV-1 infection in dendritic cells (DCs) and macrophages by regulating the expression of HIV-1 co-receptors and DC-SIGN 12,13 . In microglial cells, Meth enhanced HIV-1 transcription via NFκB/SP1 dependent activation of HIV-1 LTR 14 . Conversely, Mantri et al .…”
Section: Introductionmentioning
confidence: 93%